Evaluation of the Sensitivity to Endocrine Therapy Index and 21-Gene Breast Recurrence Score in the SWOG S8814 Trial. Issue 10 (1st April 2023) - Speers, Corey W.; Symmans, W. Fraser; Barlow, William E.; Trevarton, Alex; The, Stephanie; Du, Lili; Rae, James M.; Shak, Steven; Baehner, Rick; Sharma, Priyanka; Pusztai, Lajos; Hortobagyi, Gabriel N.; et al.
Abstract : PURPOSE: Chemotherapy has not demonstrated benefit over adjuvant endocrine therapy alone for postmenopausal patients with node-positive breast cancer with a 21-gene breast recurrence score (RS) of 25 or below (RS ≤ 25). We tested whether combined results from RS and the sensitivity to endocrine therapy (SET2, 3) index of endocrine-related transcription (SETER/PR ) adjusted for baseline prognostic index (BPI) improve prognostic assessment, and whether SET2, 3 predicted benefit from anthracycline-based chemotherapy. METHODS: A blinded retrospective clinical validation of SET2, 3 in two randomized treatment arms from the SWOG S8814 trial comparing adjuvant anthracycline-based chemotherapy followed by tamoxifen endocrine therapy for 5 years, versus tamoxifen alone. SET2, 3 assay was calibrated and measured using whole-transcriptome RNA sequence of tumor samples already tested for RS. The primary end point was disease-free survival (DFS). RESULTS: There were 106 events in 283 patients over a median follow-up of 8.99 years. Proportional hazards assumptions were met during the first 5 years only. SET2, 3 index and RS were not correlated (r = –0.04) and were independently prognostic (SET2, 3: hazard ratio [HR], 0.48 per unit; 95% CI, 0.34 to 0.68; P < .001; RS: HR, 1.28 per 10 units; 95% CI, 1.14 to 1.44; P < .001). SET2, 3 index did not predict chemotherapy benefit (interaction P = .77). SET2, 3 was high in 93/175 (53%) patients with RS ≤ 25 (concordant low-risk), with 5-year DFS 97%. SET2, 3 was low in 55/108 (51%) patients with RS > 25 (concordant high-risk), with 5-year DFS 53%. Both components of SET2, 3 index were prognostic after adjustment for RS: SETER/PR (HR, 0.65; 95% CI, 0.46 to 0.92) and BPI (HR, 0.45; 95% CI, 0.31 to 0.64). CONCLUSION: SET2, 3 index was not correlated with RS, demonstrated additive prognostic performance, and was not chemopredictive in this subset of patients from S8814. The SETER/PR and BPI components of SET2, 3 each added prognostic information to RS.